The global emissions impact of Irish consumption - Kelly C. De Bruin; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2022)
This paper calculates and compares the level of Greenhouse gas (GHG) emissions using a production-based accounting (PBA) method and a consumption based accounting (CBA) method. The PBA attributes GHG emissions resulting from production processes to the country in which the production takes place. CBA attributes these emissions instead to the country which consumes the goods produced. Our results show that emissions as calculated by the CBA method are 69% higher than when calculated applying a PBA method. This reflects that the global carbon footprint of Irish consumption is higher than what is reflected in our current PBA calculations. The main cause of higher CBA emissions is the import of goods for household consumption. Climate policies in Ireland focus on reducing PBA emission and would need to include measures to address CBA emissions to ensure Ireland's global carbon footprint is limited.
Keywords: 330; consumption; input-output analysis; consumption-based accounting; production-based accounting; climate policies; CGE